+0  
 
0
268
1
avatar
sqrt(y+1) + sqrt(y-3) = 5

i cant solve this confounded problem i need it an example
Guest Feb 28, 2012
 #1
avatar+3076 
0
arkansaw:

sqrt(y+1) + sqrt(y-3) = 5

i cant solve this confounded problem i need it an example



sqrt(y + 1) + sqrt(y - 3) = 5
sqrt(y + 1) + sqrt(y - 3) = 5 | -sqrt(y - 3)
sqrt(y + 1) = 5 - sqrt(y - 3) | ^2
y+1 = (5 - sqrt(y - 3) )^2
y+1 = 5^2- 2*5*sqrt(y - 3) + (y - 3)
y+1 = 25- 10*sqrt(y - 3) + (y - 3)
y+1 = 22- 10*sqrt(y - 3) + y | -y
1 = 22- 10*sqrt(y - 3) | -22
-21 = -10*sqrt(y - 3) | *-1
21 = 10*sqrt(y - 3) | /10
21/10 = sqrt(y - 3) | ^2
(21/10)^2 = y - 3 | +3
(21/10)^2 +3 = y
441/100 + 3 = y
441/100 + 300/100 = y
y = 741/100
y = 7.41
admin  Feb 28, 2012

17 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.